Hepatic and renal metabolism of somatostatin-like immunoreactivity. Simultaneous assessment in the dog. - Polonsky, K S (1981)
The hepatic and renal metabolism of somatostatin-like immunoreactivity (SLI) was assessed simultaneously in an in vivo dog model. The hepatic extraction of this peptide was 29.4 +/- 2.3% and was similar for endogenous and infused exogenous SLI. The renal extraction was 62.3 +/- 5%. The renal clearance of SLI was significantly greater than that of inulin indicating that the peptide is handled by peritubular uptake from postglomerular blood in addition to glomerular filtration. In both organs SLI extraction was not saturable even at arterial concentrations in excess of 100 times physiological range. The overall metabolic clearance rate of SLI was 19.7 +/- 1.6 ml/kg per minute of which 32.7 +/- 4.6% was contributed by hepatic and 37 +/- 4.9% by renal uptake mechanisms. The plasma half disappearance time of exogenously infused SLI was 1.9 +/- 0.3 min. The studies indicate that in the dog, the liver and kidney are both major sites of SLI metabolism, together accounting for 70.0 +/- 8.7% of the metabolic clearance of the peptide.